2010
DOI: 10.1007/s10751-009-0149-8
|View full text |Cite
|
Sign up to set email alerts
|

Precision laser spectroscopy without optical detection

Abstract: Laser spectroscopy of trapped ions is likely to be limited by the availability of suitable detection systems for fluorescence photons, especially in the infrared transition frequency domain. This restriction can be circumvented when ions are stored in a Penning trap with an additional magnetic field inhomogeneity which couples the ion oscillation frequencies to the oscillation energies in a well-defined way. In such a case, laser cooling (or heating) on the optical transition of interest can be detected electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…If the fluorescence is in the far infrared spectral region and difficult to detect by even the most modern photo detectors, the resonance of a single stored ion might be observed by using an inhomogeneous magnetic field that couples the ion's motion and makes in this way a cooling resonance detectable [62,63]. When the QED corrections in highly charged ions are tested and found to be valid, these measurements would enable the determination of the Bohr-Weisskopf effect in these nuclei, which is a measure of the distribution of the magnetism over the nuclear volume.…”
Section: Trends and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the fluorescence is in the far infrared spectral region and difficult to detect by even the most modern photo detectors, the resonance of a single stored ion might be observed by using an inhomogeneous magnetic field that couples the ion's motion and makes in this way a cooling resonance detectable [62,63]. When the QED corrections in highly charged ions are tested and found to be valid, these measurements would enable the determination of the Bohr-Weisskopf effect in these nuclei, which is a measure of the distribution of the magnetism over the nuclear volume.…”
Section: Trends and Future Directionsmentioning
confidence: 99%
“…Such experiments were already performed at the Livermore EBIT by Beiersdorfer, Crespo et al and in the storage ring ESR as reported by Matthias Nothelfer in Poznan (for references see [275]). Andjelkovic et al [61] and Vogel and Quint [62,63] presented the designs of the set-up and discussed the physics. Comparing the situation at HITRAP with those in the EBIT and ESR experiments, they expect less background and much higher resolving power since the ions are well localized providing a point-like source, are cooled to 4 K and therefore nearly at rest in space, and occupy one charge state only.…”
Section: New Facilitiesmentioning
confidence: 99%
“…Spectroscopic properties of highly charged ions contain valuable information both about atomic and nuclear properties of these systems and open new ways to access fundamental quantities [3,4]. Experimental approaches to precision spectroscopy especially of forbidden transitions are manifold with novel methods under implementation which also build a bridge between optical and microwave spectroscopy [5,6,7]. In doing so, they allow experimental links between transition frequencies and both electronic and nuclear magnetic moments of these ions.…”
mentioning
confidence: 99%